Cor triatriatum dexter with imperforate Ebstein's anomaly. - Gerlis, L M (1976)
A case of cor triatriatum dexter is described in which the anomalous right atrial partition is identified as the right venous valve; there is an associated anomaly of the right atrioventricular valve which combines features of Ebstein's anomaly, and an atypical, imperforate, tricuspid atresia.